PEMBERDAYAAN MASYARAKAT MELALUI DAKWAH KH. ZAINUDDIN AMIR DI BADUY LUAR - Cucun Sumiyati; Wiwi Siti Syajarotunnisa (Jurnal Kommunity Online, 2023)
Community development, presupposes that the role of a figure in changing society towards ideal conditions, is very important. This figure becomes a role model and role model for the community, then he can make social changes in society. This article concludes that strategies for community empowerment through da'wah in Baduy Luar, Leuwidamar District, Lebak Banten by KH Zaenudin include strategies that are included in five programs, namely: Providing Guidance, Providing Formal and Non-Formal Education, Improving Welfare, Providing Housing.